Dietary Intake of Polyphenols Enhances Executive/Attentional Functioning and Memory with an Improvement of the Milk Lipid Profile of Postpartum Women from Argentina - Miranda, Agustín Ramiro (2022)
Puerperium may lead to memory and executive/attentional complaints that interfere with women’s daily life. This might be prevented by dietary compounds, such as neuroprotective polyphenols. Their bioactivity depends on their effects on lipid metabolism in different tissues, such as the brain, fat, and breast. Thus, a polyphenol-related cognitive improvement may be associated with changes of lipids in human milk, which are key for infant neurodevelopment. A cross-sectional study was conducted on 75 postpartum women from Córdoba (Argentina), involving several neuropsychological tests. Diet was registered to identify polyphenol intake and food pattern adherence, with sociodemographic and other psychological variables (insomnia, stress, subjective cognitive complaints) being also studied. Triacylglycerols, cholesterol, and their oxidative forms were analyzed as milk biomarkers. Multivariate statistical methods were applied. Results confirmed that women who consumed polyphenols presented better executive/attentional performance (i.e., higher correct responses, conceptual level responses, complete categories, verbal fluency; lower attentional interferences, and perseverative errors) and word retention with lower interference. Polyphenols were positively associated with milk lipids, which were higher in women with better cognition. Furthermore, they had lower oxidized triacylglycerols. In conclusion, polyphenolic intake during postpartum may improve executive/attentional functioning, memory, and milk lipid profile.